Pre-trial process in criminal proceedings - Kamarudin, Abdul Rani; Sidek, Abd. Halim (International Law Book Services, 2002)
Pre-trial process in criminal proceedings is a specially designed edition for students who are pursuing law in various universities and private colleges. The study of criminal Proceedings under the Criminal Procedure Code, has been made easy by this book. It will be equally useful to legal practitioners and academicians.